2017
DOI: 10.1371/journal.pone.0179316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of Abbott m2000 and Roche COBAS Ampliprep/COBAS Taqman assays for HIV-1 viral load determination using dried blood spots and dried plasma spots in Kenya

Abstract: BackgroundRoutine HIV viral load testing is not widely accessible in most resource-limited settings, including Kenya. To increase access to viral load testing, alternative sample types like dried blood spots (DBS), which overcome the logistic barriers associated with plasma separation and cold chain shipment need to be considered and evaluated. The current study evaluated matched dried blood spots (DBS) and dried plasma spots (DPS) against plasma using the Abbott M 2000 (Abbott) and Roche Cobas Ampliprep/Cobas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
43
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 26 publications
9
43
2
Order By: Relevance
“…This observation of discrepant results is consistent with findings from other studies using Whatman 903 ® cards [15,2123]. The reasons of these discrepant results were well documented in the literature[15,17,2123]. In a systematic review published in 2014, Smit et al [17] have indicated that the most important reasons DBS is not, and may never be, as sensitive as plasma is because of the differences in sample volume between DBS and plasma.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This observation of discrepant results is consistent with findings from other studies using Whatman 903 ® cards [15,2123]. The reasons of these discrepant results were well documented in the literature[15,17,2123]. In a systematic review published in 2014, Smit et al [17] have indicated that the most important reasons DBS is not, and may never be, as sensitive as plasma is because of the differences in sample volume between DBS and plasma.…”
Section: Discussionsupporting
confidence: 93%
“…However, in this study, 17.0% samples tested not detected on FTA cards, were positive on plasma specimens, with 2.1% high positive. This observation of discrepant results is consistent with findings from other studies using Whatman 903 ® cards [15,2123]. The reasons of these discrepant results were well documented in the literature[15,17,2123].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, DBS samples can be stored for relatively long periods of time after collection and can be shipped without special biohazard precautions[24, 30]. These advantages have led to the use of DBS sampling for analysis beyond the neonatal period, including rapid diagnostics of vector-borne diseases[31], identification of disease-associated genetic mutations[32], diagnosis of HIV infection, and quantification of HIV VL[3336], among others.…”
Section: New Pharmacologic Measures That Quantify Cumulative Drug Expmentioning
confidence: 99%